Epidemiology, antibiograms and multilocus sequence typing of Salmonella enterica among ayam kampong (Gallus gallus domesticus Linnaeus) from South-Central Peninsular Malaysia - Jajere, Saleh Mohammed (2020)
Salmonella enterica represents an important foodborne pathogen worldwide. In Malaysia, several large foodborne disease outbreaks involving human fatalities have been linked to eating chicken and its products contaminated with Salmonella. Village chickens are presumed to be raised in a more ‘organic’ environment and have not been studied for the prevalence of Salmonella. With increasing consumer awareness on food safety issues related to chemical residues and antibiotics used in producing commercial chickens, the demand for village chickens in Malaysia and other parts of the world has increased. Consumers are willing to pay higher price for products raised in organic setups. However, the epidemiology of Salmonella infection amongst village chickens in Malaysia remains largely unknown. Thus, the current study investigates the epidemiology, antibiograms and genetic diversity of Salmonella enterica amongst village chickens from the South-central Peninsular Malaysia. Thirty-five village flocks were sampled from Selangor (n=19), Melaka (n=10), Johor (n=4), and Negeri Sembilan (n=2). In total, 1042 samples were collected; these included cloacal swabs (n=675), eggs (n=62), pooled drinking water (n=175), pooled feeds (n=70), and pooled flies (n=60). Isolation of Salmonella from these samples was carried out according to the protocols and recommendations of the World Organization for Animal Health (OIE) terrestrial manual. The prevalence of Salmonella at an individual bird-level was 2.5% (17/675, 95% CI: 1.6−4.0). All eggs screened were negative. For environmental samples, Salmonella was detected in 5.14% (9/175), 7.14% (5/70), and 5.0% (3/60) for water, feed, and flies, respectively. Thirty-four isolates and eight Salmonella serotypes were identified. S. Weltevreden (20.6%) was the most common, followed by S. Typhimurium and S. Agona (17.6%), S. Albany and S. Enteritidis (8.8%), S. Molade (5.9%), S. Corvallis and S. Schleissheim (2.9%), and others grouped as Salmonella spp. (11.8%). Multivariable logistic regression models revealed that Salmonella positivity among flocks could be strongly predicted by storage of feeds (uncovered feeds; OR=10.38; 95% CI: 1.25−86.39; p=0.030) and uncovered water tanks (uncovered tank; OR=6.43; 95% CI: 1.02−40.60; p=0.048). Among the isolates, 26.5% (n=9) were susceptible to all antibiotics, while 73.5% (n=25) were resistant to at least one antibiotic tested. Multidrug resistance was displayed by 8 isolates (23.5%). Ciprofloxacin (100%), gentamicin (97.1%), norfloxacin (97.1%), cefotaxime (97.1%) and ceftiofur (97.1%) were very effective against most isolates. The highest level of resistance was observed for tetracycline (35.3%) and streptomycin (35.3%). Eight isolates (23.5%) were MDR to two or more antibiotic agents belonging to ≥ 3 antimicrobial classes. Colistin resistance (Minimum inhibitory concentrations: 4 - 16 mg/L) was detected among 5 (14.7%) isolates comprising S. Weltevreden, S. Albany, S. Typhimurium and Salmonella spp. Representative Salmonella isolates (n=15) were examined by multilocus sequence typing (MLST) using seven housekeeping genes from the MLST online database. The Salmonella enterica serovars were resolved into 7 sequence types (STs). The ST13 (n=3) and ST11 (n=3) were the predominant STs respectively found in serovars Agona and Enteritidis, followed by ST34 (n=2) and ST36 (n=2), ST365 (n=2), ST1541 (n=2) and ST19 (n=1) respectively found in serovars Typhimurium, Weltevreden, Corvallis and Typhimurium. It was found that, with the exception of serotype Typhimurium, the MLST indicated a strong correlation between the STs and serovars. Each serovar of the Enteritidis, Agona, Weltevreden and Corvallis strains was represented unique STs. In conclusion, it was found that the prevalence of Salmonella in village chickens in the study area was lower than that reported from commercial chickens in Malaysia. Uncovered feed and water storage were strongly associated with Salmonella positivity among the village chicken flocks. The present study also demonstrated the contamination of local village chickens with MDR non-typhoidal Salmonella strains, some of which were resistant to multiple classes of antimicrobials. Generally, the level of resistance was meaningfully lower than those reported from commercial chicken carcases and its products in Malaysia and elsewhere. However, despite the minimum application of antibiotics in the free-range chicken production and lack of antibiotic growth promotion use, the resistance to colistin was observed. The exposure to natural environment such as wild birds, proximity to commercial chicken farms as well as contaminated water and soils may play complex role in determining antibiotic resistance. Molecularly, all sequence types identified among the isolates tested in the present study has been documented in Malaysia previously, and were also reported in many Asian countries including China, Singapore, Indonesia, Thailand, Vietnam and Myanmar (ST11). ST365 was also reported in Singapore. This finding highlights that these village chicken Salmonella strains are not unique and have been circulating in the Asian region in multiple animal species and humans.